Examining Success of Land Record Information Systems (LRMIS) in Pakistan: Validating an incorporated IS success model - Malik, Babur Hayat; Shuqin, Cai; Qamar, Saqib; Mattiullah, Butt (European Scientific Journal, ESJ, 2016)
Objective of this article is to investigate the success (by determining citizen’s intention to use and satisfaction) of Land Record Information Systems (LRMIS) from perspective of Pakistan. The success of this egovernment information system is investigated using an incorporated IS success model. Model formulated here features constructs such as System Quality, Service Quality, and Information Quality, Perceived Risk, Perceived Ease of Use, Perceived Satisfaction, Perceived Usefulness, Awareness, Trust, Information Security and Behavioral Intention. The suggested incorporated research model of IS was validated using feedbacks taken from 250 citizens across different cities of Pakistan. Verifiable findings showed the positive and substantial linkage between all 17 hypothesized associations of 10 different constructs. Validated data-based outcomes and argumentations provided in this research can help government to enrich upon and to completely avail the potentiality of LRMIS as serviceable and an effective computer system toward a digital, secure, lucid and uncorrupted society.